Review : Rabies Pada Rodensia Dalam Kurun Waktu 20 Tahun: RABIES PADA RODENSIA DALAM KURUN WAKTU 20 TAHUN - Permadi, Wempi Dody; Pradani, Firda Yanur (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2021)
Rodentia is an animal is still causing zoonotic diseases in humans. In several cases has reported that rabies identify in cow, bat, squirrels and rodentia. The incidences of rabies cases transmitted by rats is very low. The aim of this article to doing description rabies after 20 years last cases in rodentia. This article is using systematical review from journal, book and cases report about rabies and rodentia. From 1790 artikel is descripting about rabies and rodentia, is just 9 articles can be analiting in this review. The species rodents that positive rabies cases is Procyn sp, Mephytidae sp, Mus sp, Dypodomys sp, Rattus novergicus, Rattus losea and Bandicota sp. The conclution of this articles is from 2000 -2020 never found again indicates rabies cases in rodentia.